Using YouTube to Increase Learning Motivation as a Resource for Learning Geography in the Digital Age - Fenika, Mila; Zakiatussoleha, Zakiatussoleha; Khotimah, Oot; Zid, Muhammad (Riviera Publishing, 2024)
This research aims to determine the learning motivation of students who use YouTube as a learning resource. This research uses qualitative methods in the Geography learning material